Reflection Upon Economic Orthodoxy And State of Exception as Threats to Fundamental Rights - Silva, Matheus Fernando de Arruda e (2017)
The article consists in a reflection of theoretical character and socio-legal guidance to demonstrate that, in a situation of economic emergency, the citizens’ fundamental rights become weakened by the application of economical recipes of neoliberal character. Therefore, emerges the confrontation between an orthodox capitalism versus a humanitarian capitalism. In our reflection we consider the hypothesis of the constitution of a state of exception fact-based, not limited to the constitutional provision of state of defense and siege, that is resulted from the application of an ideology utilized by the governments that prioritize the economy over the well-being of their citizens.